2013
DOI: 10.1016/j.ijheh.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury and elemental mercury differentially associate with blood pressure among dental professionals

Abstract: Methylmercury-associated effects on the cardiovascular system have been documented though discrepancies exist, and most studied populations experience elevated methylmercury exposures. No paper has investigated the impact of low-level elemental (inorganic) mercury exposure on cardiovascular risk in humans. The purpose of this study was to increase understanding of the association between mercury exposure (methylmercury and elemental mercury) and blood pressure measures in a cohort of dental professionals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 54 publications
3
31
1
Order By: Relevance
“…To the best of our knowledge, only one study has examined this association, which also observed an inverse association between urinary mercury and SBP but in a convenience sample of male dental professions (Goodrich, 2012). This inverse association is striking but not unrealistic since several laboratory studies have shown that inorganic mercury can decrease blood pressure (Massaroni et al, 1995; Rhee and Choi, 1989; Rossoni et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge, only one study has examined this association, which also observed an inverse association between urinary mercury and SBP but in a convenience sample of male dental professions (Goodrich, 2012). This inverse association is striking but not unrealistic since several laboratory studies have shown that inorganic mercury can decrease blood pressure (Massaroni et al, 1995; Rhee and Choi, 1989; Rossoni et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Cardiovascular health effects of inorganic mercury are poorly understood, and there is no epidemiologic study that has examined the association between inorganic mercury exposure and hypertension, except for one recent pilot study by us which documented reduced SBP among male dental professionals in association with inorganic mercury exposure (Goodrich, 2012). Such an association is plausible given that several laboratory rodent studies have reported that unlike methylmercury, inorganic mercury exposure causes depressed arterial systolic pressure (Massaroni et al, 1995; Rhee and Choi, 1989; Rossoni et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…While several studies investigated chronic low dose Hg exposure and its association with subclinical effects on nervous, cardiovascular and immune systems, the true impact of chronic exposure to relevant and low doses of Hg remains uncertain and conflicted [Franzblau et al, 2012; Goodrich et al, 2012; Karagas et al, 2012; Roman et al, 2011]. While recent animal and in vitro studies suggest MeHg and I-Hg exposure may modify the epigenome, epidemiological evidence is limited to one cohort of women with blood Hg measurements [Hanna et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary mercury concentrations, reflecting exposure to IHg, have been associated with a lower SBP among United States adults in the 2003-2006 NHANES (Park et al, 2013) and dental professionals (Goodrich et al, 2013); the latter study notes this was driven by associations among males. This is consistent with our observations that inorganic mercury was associated with a lower in PP.…”
Section: Discussionmentioning
confidence: 95%